2006
DOI: 10.1097/01.aog.0000224606.26514.3a
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Age and Spontaneous Abortion

Abstract: Increasing paternal age is significantly associated with spontaneous abortion, independent of maternal age and multiple other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 38 publications
6
87
0
3
Order By: Relevance
“…This result is in line with previous studies showing an association between advanced paternal age and some congenital malformations [6,25,28,31]. Several studies have also shown that fetal death correlates with paternal age [1,9,15,19,24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in line with previous studies showing an association between advanced paternal age and some congenital malformations [6,25,28,31]. Several studies have also shown that fetal death correlates with paternal age [1,9,15,19,24].…”
Section: Discussionsupporting
confidence: 92%
“…Advanced paternal age has been associated with a higher risk of spontaneous abortions [9,15,24], stillbirth [1,19], preterm birth [2,30], congenital malformations [25,28,31], childhood cancer [10,29], epilepsy [26], autism [17,21], and schizophrenia [18,23] in the offspring. The biological mechanisms behind these associations are unknown but may be related to de novo mutations and epigenetic changes in male germ cells with short and long term health consequences for the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…The most compelling indication that paternal age may affect embryo quality is data on miscarriage. In general, the consensus from the available data is that advanced paternal age is a risk factor for miscarriage though no real mechanisms for this fi nding have been elucidated (Kleinhaus et al 2006 ;Slama et al 2005 ). Other studies evaluating ART with donor eggs (to completely remove the infl uence of maternal factors) found no associations between paternal age and risk of miscarriage (Begueria et al 2014 ).…”
Section: Embryo Quality Pregnancy Outcomes and Offspring Healthmentioning
confidence: 99%
“…In addition, serum steroid levels decrease with advancing age, reflecting altered hypothalamic-pituitary axis regulation and decreased testicular function (12). Advanced paternal age has been linked to an increased risk of miscarriage (13), a higher rate of obstetric complications such as preeclampsia (14) and disorders in the offspring, including low birth weight (15), impaired neurocognitive outcomes (16), Down syndrome (17), epilepsy (18), schizophrenia (19), diabetes mellitus (20), and breast cancer (21).…”
mentioning
confidence: 99%